A.V. Bitsadze's observation on bianalytic functions and the Schwarz problem revisited. Issue 4 (3rd April 2021) - Aksoy, Ümit; Begehr, Heinrich; Çelebi, A. Okay
Abstract : The extension of the Schwarz representation formula to simply connected domains with harmonic Green function and its polyanalytic generalization is not valid in general. They do hold only for certain domains.